2005
DOI: 10.1111/j.1365-2672.2005.02709.x
|View full text |Cite
|
Sign up to set email alerts
|

Rotavirus vp7 antigen produced by Lactococcus lactis induces neutralizing antibodies in mice

Abstract: C . A . P E R E Z , C . E I C H W A L D , O . B U R R O N E A N D D . D E M E N D O Z A . 2005.Aims: To determine if live recombinant Lactococcus lactis strains expressing rotavirus VP7 antigen are immunogenic in mice. Methods and Results: Using the food-grade lactic acid bacterium L. lactis as a carrier, we expressed VP7, the major rotavirus outer shell protein and one of the main components of the infective particle, as a cytoplasmic, secreted or cell wall anchored forms. Our results showed that recombinant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(28 citation statements)
references
References 28 publications
1
26
0
1
Order By: Relevance
“…L. lactis expressing cell wallanchored Rotavirus VP7 has also been investigated as an oral vaccine candidate. However, when sera from individually immunized mice were examined only 3 out of 10 sera showed specific reactivity with VP7 [22]. Finally recent work has demonstrated that L. lactis expressing domain III of the major dengue virus envelope protein E (EDIII) may provide a successful vaccine platform when administered either orally or intranasally, although results varied between mouse strains used [23].…”
Section: Overview Of Vaccination Studies Utili-zing Engineered L Lacmentioning
confidence: 95%
“…L. lactis expressing cell wallanchored Rotavirus VP7 has also been investigated as an oral vaccine candidate. However, when sera from individually immunized mice were examined only 3 out of 10 sera showed specific reactivity with VP7 [22]. Finally recent work has demonstrated that L. lactis expressing domain III of the major dengue virus envelope protein E (EDIII) may provide a successful vaccine platform when administered either orally or intranasally, although results varied between mouse strains used [23].…”
Section: Overview Of Vaccination Studies Utili-zing Engineered L Lacmentioning
confidence: 95%
“…(B) Protection against rotavirus challenge. The immunized mice were challenged (by oral gavage) with 100 ID 50 per mouse with a murine strain (EDIM EW) rotavirus 3 weeks after the final immunization. Virus shedding in feces, as determined by an ELISA for detecting rotavirus antigen, is given as A 450 values Ϯ standard errors of the means (SEM).…”
Section: Resultsmentioning
confidence: 99%
“…Oral immunization with recombinants of either Salmonella enterica serovar Typhimurium or Lactobacillus lactis expressing rotavirus virion protein 7 (VP7) generated immune responses after oral administration to mice, but no challenge studies were reported (50,58).…”
mentioning
confidence: 99%
“…However, genetically modified versions of this microorganism are still effective in delivering antigens to the mucosal immune system and capable of inducing a local immune response (Robinson et al, 1997;Maassen et al, 1999;AdelPatient et al, 2005;Perez et al, 2005). This seems to happen because L. lactis lacks the ability to multiply in vivo but it can readily be sampled by dendritic cells.…”
Section: Discussionmentioning
confidence: 99%